Readiness of Madrasah Ibtidaiyah in Pati Regency in Implementing the "Kurikulum Merdeka" - Melisa Yusrina; Agus Syakroni; Irma Nur Af'idah; M Sofyan Alnashr (Research Journal on Teacher Professional Development, 2023)
The “Kurikulum Merdeka” (Independent Curriculum) is a mandate from the Ministry of Education and Culture and the Ministry of Religious Affairs for organizers of educational institutions, including madrasah. This research aims to find out how the readiness of Madrasah Ibtidaiyah (MI) in Pati Regency in implementing the independent curriculum according to government policy. This research is a field study with a descriptive qualitative approach. Data were collected through observation, interview, and documentation and then analyzed using Miles and Huberman interactive analysis. The results showed that MIN 2 Pati and MI Al-Fattah Juwana as madrasahs in Pati Regency that were used as pilot projects were not fully prepared for the implementation of the independent curriculum. Training related to curriculum implementation has been carried out, but at the practical level there are still some obstacles. These obstacles include the lack of intensive training, the lack of teacher motivation to improve, and the low level of innovation in education implementation. Supporting facilities and infrastructure are also not well available in both madrasas. The Pati Regency Ministry of Religious Affairs always provides encouragement and assistance in implementing the independent curriculum, starting from intensive training, mentoring, and other supporting infrastructure. Although there are still some obstacles, the independent curriculum at the Madrasah Ibtidaiyah level must be carried out as well as possible so that educational goals will be achieved.